2020
DOI: 10.1515/dmpt-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 in the light of epidemic disease described in Unani medicine

Abstract: Unani system of medicine is based on the humoral theory postulated by Hippocrates, according to him the state of body health and disease are regulated by qualitative and quantitative equilibrium of four humours. Amraz-e-Waba is an umbrella term which is used in Unani medicine for all types of epidemics (smallpox, measles, plague, Hameer Saifi, influenza, Nipaha, Ebola, Zika, and 2019 novel coronavirus, etc.) mostly fatal in nature. The coronavirus disease 2019 (COVID-19) is a severe acute respiratory infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…We found that Damwi mizaj (sanguine temperament) was seen predominantly in all patients irrespective of the treatment given. Sanguine is considered a combination of two qualities; hot and moist and according to the Unani concept, infectious disease developed due to abnormal dominance of hot (Hararat), moist (Ratoobat), and microbes ( Ajsam-e-Khabisa) [29]. The finding suggested that people of sanguine temperament was associated with increased susceptibility to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Damwi mizaj (sanguine temperament) was seen predominantly in all patients irrespective of the treatment given. Sanguine is considered a combination of two qualities; hot and moist and according to the Unani concept, infectious disease developed due to abnormal dominance of hot (Hararat), moist (Ratoobat), and microbes ( Ajsam-e-Khabisa) [29]. The finding suggested that people of sanguine temperament was associated with increased susceptibility to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…but the clinical features of COVID-19 resemble with those of Nazla-e-Wabaiya, a type of Amraze-Waba (epidemic disease) which was well described many years ago in Unani text such as high-grade fever, headache, nausea and vomiting, running nose, dry cough, respiratory distress, alternate and small pulse, asthenia, foul smell from breath, insomnia, frothy stool, syncope, coldness in both upper and lower extremities, etc. [4,5] Although the majority of people with COVID-19 have uncomplicated or mild illness (81%), some will develop severe illness requiring oxygen therapy (14%) and approximately 5% will require intensive care unit treatment. Of those critically ill, most will require mechanical ventilation [6] .…”
Section: Concept Of Epidemic Disease (Amraz-e-waba) In Unani Medicinementioning
confidence: 99%
“…• The diet which is not easily digestible, hot, spicy and oily diet should be avoided. • Sweets, alcohol, and meat of fish should be avoided [5] .…”
Section: Diet Restrictedmentioning
confidence: 99%
See 1 more Smart Citation